Towards Shared Research Participatory and Integrative Approaches in Researching African Environments - Haller, Tobias; Zingerli, Claudia (Kultur und soziale Praxis, 2020)
Intercultural, interdisciplinary, and transdisciplinary research interfaces confront researchers with considerable challenges. Towards Shared Research portrays how scholars from different disciplinary and geographical origins and at various academic career stages strive for a more inclusive and better understanding of knowledge about African environments. The book is addressed to researchers, facilitators, and policy-makers to make a case for participatory and integrative approaches resulting in systemic and co-created analyses.